Avaliação da qualidade química e biológica do solo em sistema de cultivo em ambiente de savana - Silva, Danielly Teixeira da (2013)
Evaluation of soil properties has grown due to the effects of management practices on soil quality. In this work had as objective to evaluate soil quality, based on the chemical and biological indicators of soil quality in environments subject to different uses, including natural savannah, planting sugar cane, forestry with sabiá, crop rotation with cassava + maize + beans, coconut based on agricultural of ecology base in the savanna of Roraima. The study was carried out in the experimental unit of the Agricultural Science Center – CCA, Campus Cauamé of Federal University of Roraima - UFRR, Boa Vista - RR. In each study environment were opened four mini-trenches, and collected soil samples at depths from 0.0 - 0.05 m, 0.05 - 0.10 m, 0.10 – 0.20 m and 0.20 - 0.40 cm, a total of 16 soil samples per area and a total of 80 soil samples to be analyzed. The samples were taken to the laboratory for soil chemical and organic matter analysis. The amounts of organic matter were higher for areas cultivated with sugarcane, ranging from 2.56 to 0.60 g kg-1 at different depths. The cultivation of MMF also obtained high values (2.25 to 0.37 g kg-1). Lower results were observed for treatments coconut (0.81 to 0.97 g kg-1), sabiá (0.70-0.98 g kg-1) and savanna (0.73 to 0.85 g kg-1) which significant differences occurred in both depths and among treatments. Treatments MMF and sugarcane had higher CEC values due to higher levels of organic matter, into the different depths. As the soil class was the same for all treatments (Oxisol), organic matter is responsible for increase of the negative charges of soil. The base saturation (V%) showed higher values for sugarcane (56.82 to 64.20%), followed by coconut and MMF (36.38 to 47.32% and 45.29 to 49.72% respectively). The sabiá (7.48 to 12.92%) and savanna (5.58 to 13.95%) had lower values. The results show that sugarcane, coconut and MMF were treatments that most contributed to increase the cationic (K, Ca, and Mg) in the soil solution. The C-CO2 released into 0.0 - 0.05 m in all areas after 20 days showed satisfactory growth and after 25 days only the sabiá had increased relative to the other areas, while in the layer of 0.05 - 0.10 m. As the biological diversity for the primer used, or selected groups by time or by treatment showed that the groups are rather heterogeneous as showed in the dendrogram, however, the data suggests further studies in additional experiments more conclusive and effective for PCR –DGGE analysis.